Nickel Extractivism and Environmental (In)security in Eastern Indonesia: An Integrated Eco-Justice Framework - Sayyidah Ilman Nisa (UNIDA Gontor, 2026)
The global energy transition to renewable energy through electric vehicles has resulted in a huge increase in demand for nickel. Indonesia is the world’s largest nickel producer, with major mining activities concentrated in the eastern regions of Central Sulawesi, South Sulawesi, South-east Sulawesi, and North Maluku. Although nickel mining has generated economic benefits, its ecological consequences have been considerably more significant, driven by foreign corporate investment within global extractive structures. This study aims to analyze the patterns and mechanisms of nickel mining activities and their environmental impacts in eastern Indonesia. Using a descriptive qualitative approach based on a literature review, this study integrates three analytical frameworks; ecological imperialism, environmental security and Fiqh Al-Bi’ah. The findings show that nickel extractivism produces systematic ecological degradation that contributes to environmental insecurity. By integrating ecological imperialism, environmental security, and Fiqh Al-Bi’ah, this study proposes an Integrated Eco-Justice Framework as a conceptual framework for explaining the structural roots of ecological injustice while providing a normative basis for environmentally just mining governance. The framework emphasizes the principles of amanah, justice, balance, and public benefit (maslahah) that uphold human dignity (karomah insaniyyah) in line with the objectives of Maqashid Al-Sharia. This study concludes that addressing the ecological impacts of nickel mining in Indonesia requires an Integrated Eco-Justice Framework grounded in Fiqh Al-Bi’ah. Such a framework provides normative guidance for responsible natural resource governance by emphasizing environmental stewardship, balance (tawazun), moderation (wasatiyyah), and human responsibility in preventing environmental degradation.